Critical Analysis of the Implementation of Thariqah As-Syam’iyyah As-Syafahiyah in Enhancing Oral Competence in Arabic Language Learning - Mochamad Mu'izzuddin; Hilda Rustiana (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study aims to critically analyze the characteristics, strengths, weaknesses, and effectiveness of implementing Thariqah As-Syam’iyyah As-Syafahiyah (Audiolingual method) in Arabic language learning. Despite its long-standing use, challenges remain in its application, which often falls into mechanistic processes without deep meaningful understanding. Design/methods/approach The research method employed is descriptive qualitative with a library research approach. Data were collected through scientific literature, journals, and relevant textbooks, then analyzed using content analysis techniques. Findings – The results indicate that this method is highly effective in forming accurate pronunciation habits and mastering standardized sentence patterns through repetition techniques (stimulus-response). Research implications – However, its success heavily depends on the educator's creativity in modifying drills to avoid boredom and the ability to integrate visual media and language laboratory technology. This study recommends a swift transition from pattern drills to contextual communication to ensure students do not merely